Comprehensive approach to type 2 diabetes mellitus: Crucial links to obesity, kidney and cardiovascular disease - Moura , Pedro Henrique; Olmedo, María Luisa Hermosilla de (Seven Editora, 2023)
Type 2 Diabetes Mellitus (DM2) is a systematic inflammatory disease with high prevalence and incidence worldwide. The objective of this article is to make an updated review of the disease, its new definitions, the cardiovascular and renal risk and other pathologies that it entails, as well as its incidence in overweight and obese patients. This document focuses on addressing the most relevant pathophysiological and clinical aspects of the disease. DOI:https://doi.org/10.56238/interdiinovationscrese-084